2013
DOI: 10.1093/neuonc/not032
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab is associated with improved survival for aggressive B cell CNS lymphoma

Abstract: In this retrospective analysis, the addition of rituximab to high-dose methotrexate-based chemotherapy in patients with aggressive B cell CNS lymphoma was associated with improved overall survival. Further studies are underway to prospectively validate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 27 publications
2
27
1
Order By: Relevance
“…In contrast to our results, a few retrospective studies have noted improved outcome in patients with PCNSL treated with combined rituximab and MTX‐based therapy . However, due to differing treatment schedules, doses delivered and patient heterogeneity, drawing comparisons is challenging.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, a few retrospective studies have noted improved outcome in patients with PCNSL treated with combined rituximab and MTX‐based therapy . However, due to differing treatment schedules, doses delivered and patient heterogeneity, drawing comparisons is challenging.…”
Section: Discussioncontrasting
confidence: 99%
“…While their findings appear superior to our results (CR 37% for the rituximab arm, six month PFS 44%), this may again largely reflect differing treatment protocols and baseline patient demographics. A retrospective multicentre study from Australia compared patients receiving chemo‐immunotherapy ( n = 18) versus chemotherapy alone ( n = 99), and found that the inclusion of rituximab was associated with a better median OS (not reached versus 40 months, P = 0.023) . However, chemotherapy delivered included varying doses of HDMTX used (2 to 8 g/m 2 ), the incorporation of cytarabine in some patients and the higher dose of rituximab administered (500 mg/m 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study represents the largest retrospective series, outside of clinical trials, that evaluates the utility of rituximab as an adjunct to cytotoxic therapy in PCNSL, showing similar results to most retrospective series of improved outcomes in PCNSL (Holdhoff et al , ; Birnbaum et al , ; Gregory et al , ). Doses of MTX and/or rituximab, use of additional cytotoxics and number of cycles were variable across these studies.…”
Section: Discussionsupporting
confidence: 69%
“…6 nature of the published studies. 13,14 Ongoing large prospective trials, such as the NCT01011920 and NTR2427, should help to establish the role of additional rituximab for PCNSL treatment. 15 Unfortunately, although patients initially respond to treatment, relapse is not uncommon.…”
Section: Discussionmentioning
confidence: 99%